2021
DOI: 10.3389/fpos.2021.642510
|View full text |Cite
|
Sign up to set email alerts
|

Different Conspiracy Theories Have Different Psychological and Social Determinants: Comparison of Three Theories About the Origins of the COVID-19 Virus in a Representative Sample of the UK Population

Abstract: COVID-19 conspiracy theories have proliferated during the global pandemic, and their rapid spread among certain groups may jeopardize the public health response (e.g., undermining motivation to engage in social distancing and willingness to vaccinate against the virus). Using survey data from two waves of a nationally representative, longitudinal study of life in lockdown in the United Kingdom (N = 1,406), we analyze the factors associated with belief in three origin theories related to COVID-19, namely that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 80 publications
3
52
0
2
Order By: Relevance
“…Consistent with previous research (Achimescu et al, 2020;Alper et al, 2020;Constantinou et al, 2020;De Coninck et al, 2021;Duplaga, 2020;Farias & Pilati, 2021;Georgiou et al, 2020;Hartman et al, 2020;Hornik et al, 2021;Kuhn et al, 2021;Pizarro et al, 2020;Romer & Jamieson, 2020;Sallam et al, 2021;van Mulukom et al, 2020;Zakharova et al, 2021), we found that sociostructural variables, such as age, educational level, political orientation, socioeconomic status, and gender are associated with conspiracy beliefs about COVID-19 and beliefs about vaccine effectiveness. As van Prooijen (2017) suggests, they are probably part of a complex interplay of socio-structural factors rather than individual predictors.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous research (Achimescu et al, 2020;Alper et al, 2020;Constantinou et al, 2020;De Coninck et al, 2021;Duplaga, 2020;Farias & Pilati, 2021;Georgiou et al, 2020;Hartman et al, 2020;Hornik et al, 2021;Kuhn et al, 2021;Pizarro et al, 2020;Romer & Jamieson, 2020;Sallam et al, 2021;van Mulukom et al, 2020;Zakharova et al, 2021), we found that sociostructural variables, such as age, educational level, political orientation, socioeconomic status, and gender are associated with conspiracy beliefs about COVID-19 and beliefs about vaccine effectiveness. As van Prooijen (2017) suggests, they are probably part of a complex interplay of socio-structural factors rather than individual predictors.…”
Section: Discussionsupporting
confidence: 92%
“…Experimentally manipulating threat salience of COVID-19 led to increased feelings of fear and anxiety, which in turn was associated with belief in conspiracy theories ( Jutzi et al, 2020 ), providing evidence for threat salience as an antecedent of later conspiracy belief. COVID-19 conspiracy beliefs have also been associated with greater anxiety more broadly ( Hartman et al, 2021 ; Kim and Kim, 2021 ; Radnitz and Hsiao, 2020 ; Sallam et al, 2020a , 2020b ; Šrol et al, 2021 , 2022 ). Similarly, risk perception, including both infection-related risks and consequence-related anxiety, was a consistent predictor of COVID-19 conspiracy beliefs ( Kim and Kim, 2021 ; Pizarro et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…This effect may be associated with lower levels of trust and higher levels of experienced threat in these individuals. Similarly, individuals with lower (vs. higher) income tend to hold stronger beliefs in COVID-19 conspiracy theories ( Constantinou et al, 2020 ; Hornik et al, 2021 ; Romer and Jamieson, 2020 ; Sallam et al, 2020a , 2020b ; van Mulukom, 2021 ), as do individuals with lower (vs. higher) levels of education ( Achimescu et al, 2021 ; Constantinou et al, 2020 ; De Coninck et al, 2021 ; Duplaga, 2020 ; Georgiou et al, 2020 ; Hartman et al, 2021 ; Hornik et al, 2021 ; Kuhn et al, 2021 ; Pizarro et al, 2020 ; Romer and Jamieson, 2020 ; Sallam et al, 2020b , 2021 ; van Mulukom, 2021 ), which may be associated with lower levels of information. Again, effects may vary according to the type of conspiracy theory.…”
Section: Resultsmentioning
confidence: 99%
“…Information, including misinformation and conspiracy theories, about vaccines plays a large role in shaping concerns related to vaccine hesitancy, 23 , 24 , 37 , 38 particularly during the COVID-19 pandemic. 39 , 40 , 41 , 42 , 43 , 44 , 45 For example, one content analysis of anti-vaccination websites found that conspiracy theories were present on every website analyzed, and that misinformation, such as the misrepresentation of vaccine studies, was extensive. 21 …”
Section: Literature Review and Frameworkmentioning
confidence: 99%